2020
DOI: 10.1101/2020.07.31.230250
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intermitochondrial signaling regulates the uniform distribution of stationary mitochondria in axons

Abstract: In the central nervous system, many neurons develop axonal arbors that are crucial for information processing. Previous studies have demonstrated that premature axons contain motile and stationary mitochondria, and their balance is important for axonal arborization. However, the mechanisms by which neurons determine the positions of stationary mitochondria as well as their turnover remain to be elucidated. In this study, we investigated the regulation of spatiotemporal group dynamics of stationary mitochondria… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…By labeling with MitoTracker, both motile and stationary mitochondria were observed in axons of control CGNs at 3 DIV (Fig. 4A), consistent with the previous report (Matsumoto et al, 2022). In CGN axons treated with 3-NT for 8 hours, mitochondria tended to remain stationary during observation (Fig.…”
Section: -Nt Inhibited Mitochondrial Motilitysupporting
confidence: 90%
See 1 more Smart Citation
“…By labeling with MitoTracker, both motile and stationary mitochondria were observed in axons of control CGNs at 3 DIV (Fig. 4A), consistent with the previous report (Matsumoto et al, 2022). In CGN axons treated with 3-NT for 8 hours, mitochondria tended to remain stationary during observation (Fig.…”
Section: -Nt Inhibited Mitochondrial Motilitysupporting
confidence: 90%
“…Animals had access to food and water ad libitum. CGNs were prepared from Jcl:ICR mice (CLEA Japan, Tokyo, Japan) at postnatal days 4 to 6 as described previously (Kubota et al, 2013, Matsumoto et al, 2022. Following decapitation, isolated cerebellar were digested with trypsin (10 mg/ml)-DNase (200 units/ml) (TRL, DP, Worthington, Lakewood, NJ) solution.…”
Section: Primary Culture Of Cgnsmentioning
confidence: 99%
“…C. elegans develops rapidly compared with other animals, reaching adulthood in 3 d, and the PLM axon elongates at a rate of ∼10 μm/h, as measured by Mondal et al (2021) . Consistent with reports on cell culture and explants ( Miller and Sheetz, 2004 ; Lamoureux et al, 2010 ; Matsumoto et al, 2020 ), Mondal et al (2021) observed that new mitochondria were added to the developing neuron between pairs of stationary mitochondria. These new additions occur at a rate of ∼0.6 mitochondria/h, further highlighting the need for prolonged imaging sessions to observe a sufficient number of events.…”
supporting
confidence: 72%
“…New mitochondrion addition during growth and axon stretching has been shown to occur between adjacent pairs of stationary mitochondria ( Miller and Sheetz, 2004 ; Lamoureux et al, 2010 ; Misko et al, 2012 ; Matsumoto et al, 2020 ). Our data are consistent with prior observations where we see a uniform distribution of mitochondria, proportionate growth of the neuron, and addition of mitochondria occurring anywhere along the process between two stationary mitochondria ( Fig.…”
Section: Discussionmentioning
confidence: 99%